Trophic discrimination factors of stable carbon and nitrogen isotopes in hair of corn fed wild boar - Holá, Michaela; Ježek, Miloš; Kušta, Tomáš; Košatová, Michaela (PloS one, 2015)
Stable isotope measurements are increasingly being used to gain insights into the nutritional ecology of many wildlife species and their role in ecosystem structure and function. Such studies require estimations of trophic discrimination factors (i.e. differences in the isotopic ratio between the consumer and its diet). Although trophic discrimination factors are tissue- and species-specific, researchers often rely on generalized, and fixed trophic discrimination factors that have not been experimentally derived. In this experimental study, captive wild boar (Sus scrofa) were fed a controlled diet of corn (Zea mays), a popular and increasingly dominant food source for wild boar in the Czech Republic and elsewhere in Europe, and trophic discrimination factors for stable carbon (Δ13C) and nitrogen (Δ15N) isotopes were determined from hair samples. The mean Δ13C and Δ15N in wild boar hair were -2.3‰ and +3.5‰, respectively. Also, in order to facilitate future derivations of isotopic measurements along wild boar hair, we calculated the average hair growth rate to be 1.1 mm d(-1). Our results serve as a baseline for interpreting isotopic patterns of free-ranging wild boar in current European agricultural landscapes. However, future research is needed in order to provide a broader understanding of the processes underlying the variation in trophic discrimination factors of carbon and nitrogen across of variety of diet types.
Keywords: Sus scrofa; Hair; Food Chain; Nutritional Status; zvířata; Zea mays; Diet; izotopy uhlíku; Nitrogen Isotopes; izotopy dusíku; nutriční stav; mužské pohlaví; vlasy, chlupy; Carbon Isotopes; kukuřice setá; dieta; potravní řetězec; Animals; Male